2012
DOI: 10.1509/jmr.10.0167
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trendspotting

Abstract: Trendspotting has become an important marketing intelligence tool for identifying and tracking general tendencies in consumer interest and behavior. Currently, trendspotting is done either qualitatively by trend hunters, who comb through everyday life in search of signs indicating major shifts in consumer needs and wants, or quantitatively by analysts, who monitor individual indicators, such as how many times a keyword has been searched, blogged, or tweeted online. In this study, the authors demonstrate how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 24 publications
1
58
1
Order By: Relevance
“…Customer engaging -the core marketing capability -puts pressure on firms to deliver superior customer value, which in turn strengthens customer intimacy to a company and its product offerings (Day & Moorman, 2010). With the market sensing capability, a firm is able to anticipate and act on market trends, weak signals and events that inform the changing customer needs and market environment (Day, 1994;Du & Kamakura, 2012), thus providing a basis for creating superior customer value. Partner linking nurtures organizational sense-making by offering opportunities of communications with network ties and access to diverse information sources and resources (e.g., Dyer & Singh, 1998;Mu & Di Benedetto, 2012;Teece, 2007).…”
Section: Marketing Capability: An Outside-in Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…Customer engaging -the core marketing capability -puts pressure on firms to deliver superior customer value, which in turn strengthens customer intimacy to a company and its product offerings (Day & Moorman, 2010). With the market sensing capability, a firm is able to anticipate and act on market trends, weak signals and events that inform the changing customer needs and market environment (Day, 1994;Du & Kamakura, 2012), thus providing a basis for creating superior customer value. Partner linking nurtures organizational sense-making by offering opportunities of communications with network ties and access to diverse information sources and resources (e.g., Dyer & Singh, 1998;Mu & Di Benedetto, 2012;Teece, 2007).…”
Section: Marketing Capability: An Outside-in Perspectivementioning
confidence: 99%
“…Market sensing capability thus helps a firm to be alert and vigilant to market trend and opportunity discovery. By mapping out the trajectory of market trend, encoding and assigning meaning to environmental cues, a firm is able to recognize emergent patterns in market environment, detecting and creating opportunities for successful development of new products that can capture both existing and latent customer needs and respond to changes in market conditions ahead of competitors (Day, 1994;Du & Kamakura, 2012;Teece, 2007).…”
Section: Market Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…This measurability adds to theory development because quantitative studies can enable trend spotting. Du and Kamakura (2012) found that a multivariate quantitative approach to trend spotting is a useful method of gathering market intelligence for creating and refining theory. Quantitative models have been a default tool for operation management research for many years (Bertrand & Fransoo, 2002).…”
Section: Relationship Between Research and Theory And How Research Comentioning
confidence: 99%
“…First, they allow advertisers to identify new topics that are gaining interest or 'trending' rapidly across the platform (Du and Kamakura, 2012). Trending topics are increasingly displayed on social media such as Twitter and Facebook, and on news sites such as the BBC.…”
Section: Introductionmentioning
confidence: 99%